When patients become teachers: perspectives from surgical residents and students - Kohn, Daniel; Prescott, Judaja; Alapati, Amulya; Mourad, Youssef; Kiarie, Patrick; Quang, Camille Mai-Phuong Tran; Jasmin, Michael; Louis, Martine A. (International Surgery Journal, 2025)
The medical field is evolving rapidly, with an increasing focus on technology to address complex medical issues. In the traditional clinical encounter, the physician’s role is often seen as providing one-way technical expertise. However, every patient-physician interaction is a two-way relationship with the potential for reciprocal learning. In the relational model of patient-physician relationships, the patient is more than a passive bystander but also an integral participant and a teacher from whom physicians can learn invaluable insights, such as the interplay of emotional intelligence and the healing process. These insights can add to the heart of the profession beyond purely academic pursuits. From a senior surgical resident’s point of view, we explore the question: What do physicians learn from patients during the therapeutic relationship that extends beyond our technological tools?